2020
DOI: 10.21708/avb.2020.14.3.9280
|View full text |Cite
|
Sign up to set email alerts
|

Isolated lateral meniscus rupture in dogs: case report

Abstract: Menisci are important intra-articular structures whose main function is attributed to load transmission and impact absorption, reducing biomechanical stress and providing greater osteoarticular stability. In dogs, knee-related disorders are described as the main causes of claudication. This report aims to describe a case of lateral meniscal lesion in a canine without signs of femorotibiopatellar instability, whose main change was claudication. The diagnosis was confirmed through orthopedic evaluation and magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…OCD is rarely reported in conjunction with meniscal damage in cats 2 . Meniscal tears in cats have been reported to occur concurrently to the above‐described pathologies, and also alongside patellar luxation 8 . To the authors’ knowledge, an isolated meniscal tear has not yet been reported in cats.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…OCD is rarely reported in conjunction with meniscal damage in cats 2 . Meniscal tears in cats have been reported to occur concurrently to the above‐described pathologies, and also alongside patellar luxation 8 . To the authors’ knowledge, an isolated meniscal tear has not yet been reported in cats.…”
Section: Introductionmentioning
confidence: 89%
“…2 Meniscal tears in cats have been reported to occur concurrently to the abovedescribed pathologies, and also alongside patellar luxation. 8 To the authors' knowledge, an isolated meniscal tear has not yet been reported in cats. The condition has been rarely reported in dogs.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations